2010
DOI: 10.1590/s1807-76922010000400003
|View full text |Cite
|
Sign up to set email alerts
|

The regional concentration of industries and the performance of firms: a multilevel approach

Abstract: This paper presents the results of a study whose objective was to understand how location within industrial concentrations, like clusters or industrial districts, affects the financial performance of firms. In its theoretical framework, this paper attempts to introduce the reasons behind the alleged superior performance of firms located in these concentrations, the base of the hypothesis formulated in this study. Analysis from a three-level hierarchical linear model applied to a sample of 509 companies located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
2
2
0
1
Order By: Relevance
“…This result is consistent with the research results by Ferreira, Goldszmidt and Csillag (2010), who analyzed the relationship between the regional concentration of industries and superior performance. The results found by these authors indicate that the location of companies and how a city interacts with an industry have considerable influence on how they will perform.…”
Section: H2supporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the research results by Ferreira, Goldszmidt and Csillag (2010), who analyzed the relationship between the regional concentration of industries and superior performance. The results found by these authors indicate that the location of companies and how a city interacts with an industry have considerable influence on how they will perform.…”
Section: H2supporting
confidence: 93%
“…However, Ferreira, Goldszmidt and Csillag (2010) provide evidence that partially contradict that statement. The authors identified that the influence of location on company performance may be higher or lower according to the location.…”
Section: Introductionmentioning
confidence: 90%
“…This result is supported by the studies of Swaminathan et.al (2015), Ferreira et. al (2010), Gabe (2008), Hollis (2003) and Yotopoulos and Nugent as cited by Holz (2010) who found insignificant relationships between industry concentration and economic performance; and linkage and growth nexus.…”
Section: Extent Of Relationship Between the Agriculture Industry Concentration And Agriculture Growthsupporting
confidence: 79%
“…Accounting-based ratios represent the most simple approach as ratios related to profitability, e.g., Return-on-Assets (ROA) or Return-on Sales (ROS) are used in the study of agglomeration economies, since they measure the earning capability of firms and provides supplementary and less biased indicator of profitability (Diez-Vial, 2011;Ferreira et al, 2010;Jennen & Verwijmeren, 2010;Kukalis, 2010). These financial ratios are not without limitations as they are calculated using numbers from financial statements influencing by company-specific accounting policies.…”
Section: Dependent Variablesmentioning
confidence: 99%